2008
DOI: 10.5194/nhess-8-377-2008
|View full text |Cite
|
Sign up to set email alerts
|

Age distribution of fossil landslides in the Tyrol (Austria) and its surrounding areas

Abstract: Abstract. Some of the largest mass movements in the Alps cluster spatially in the Tyrol (Austria). Fault-related valley deepening and coalescence of brittle discontinuities structurally controlled the progressive failure and the kinematics of several slopes. To evaluate the spatial and temporal landslide distribution, a first comprehensive compilation of dated mass movements in the Eastern Alps has been made. At present, more than 480 different landslides in the Tyrol and its surrounding areas, including some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
166
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(173 citation statements)
references
References 39 publications
(58 reference statements)
5
166
1
1
Order By: Relevance
“…This finding was both a surprise and a concern to researchers in the European Alps, who had previously assumed that the ancient large landslides were a relic of deglaciation and not a phenomenon that had occurred under climatic conditions similar to present (Abele, 1997). While some major landslides initiated prior to deglaciation (Ambrosi and Crosta, 2006), and some were synchronous with deglaciation (Agliardi et al, 2001;Smith, 2001), the majority of documented cases indicates that large post-glacial failures have typically occurred some thousands of years after ice retreat ( This is a view that is consistent amongst several researchers who link climate changes with increased landslide activity, including debris-and earth-flows Matthews et al, 1997;Dapples et al, 2002;Bertolini et al, 2004;Soldati et al, 2004;Prager et al, 2007;Prager et al, 2008). Abele (1997) however, suggested that it is unlikely that temporal patterns of large, deep-seated rock slope failures would match climatic patterns.…”
Section: Late-glacial-late-holocenementioning
confidence: 56%
“…This finding was both a surprise and a concern to researchers in the European Alps, who had previously assumed that the ancient large landslides were a relic of deglaciation and not a phenomenon that had occurred under climatic conditions similar to present (Abele, 1997). While some major landslides initiated prior to deglaciation (Ambrosi and Crosta, 2006), and some were synchronous with deglaciation (Agliardi et al, 2001;Smith, 2001), the majority of documented cases indicates that large post-glacial failures have typically occurred some thousands of years after ice retreat ( This is a view that is consistent amongst several researchers who link climate changes with increased landslide activity, including debris-and earth-flows Matthews et al, 1997;Dapples et al, 2002;Bertolini et al, 2004;Soldati et al, 2004;Prager et al, 2007;Prager et al, 2008). Abele (1997) however, suggested that it is unlikely that temporal patterns of large, deep-seated rock slope failures would match climatic patterns.…”
Section: Late-glacial-late-holocenementioning
confidence: 56%
“…Some of these preparatory conditions include gradual rock weathering, frost action, changes in pore water pressure and stress redistribution during or after glacial unloading (e.g. Gunzburger et al 2005;Prager et al 2008;Korup et al 2010). Important triggering factors are heavy rainfall or earthquakes, which have as a consequence a direct collapse of the slope, as shown by more recent events in Alpine realm (Fritsche and Fäh 2009).…”
mentioning
confidence: 99%
“…Brückl and Parotidis (2005) introduced the concept of subcritical crack growth as the process which controls the velocity of quasicontinuous deformation of the main body of a mass movement, but also the sliding velocity at the basal surface of rupture. Prager et al (2008Prager et al ( , 2011) also considered subcritical crack growth as a process controlling the development of DGSD. According to Brückl and Parotidis (2005), one fundamental idea is that asperities at the sliding surface must be overcome by subcritical crack growth.…”
Section: Relation Of Displacement Rate To Hydrological Parameters Prementioning
confidence: 99%
“…The other deformation network points are at most 150 m away from the strain rosette. Network surveys were carried out in June of 2007, 2008, 2009and in December 2011. Five sets of slant distances, directions, and zenith distances were observed at three network points during each survey.…”
Section: Wire Extensometermentioning
confidence: 99%